DISTRIBUTION AND GEOCHEMICAL APPLICATIONS OF AROMATIC HYDROCARBONS IN CRUDE OILS - Asif, Muhammad; Tahira, Fazeelat (Journal of Research (Science), 2007)
Distribution of aromatic hydrocarbons was studied in a set of crude oils, five from northern Indus basin of potwar area and two from southern Indus basin. Diaromatic and triaromatic hydrocarbons were separated from highly complex mixture of sedimentary organic matter by using liquid chromatography techniques such as column chromatography, TLC and GC-FID. These classes of compounds were identified to alkylated isomers of naphthalenes and phenanthrenes by using reference chromatograms and literature data. High concentration of di-, tri- and tetra-methyl naphthalenes was observed in all crude oils except Kal#1. The relative increase in concentration of alkyl naphthalenes was found as moved to higher methyl substituted isomers. This suggests that they are the product of sedimentary alkylation reactions during catagensis and metagensis. The significant concentration of methyl phenanthrenes indicated source of organic matter. High levels of both 1-MP and 9-MP showed marine and terrestrial source of organic matter except Umer crude oil which is most likely to have terrestrial origin. The ratios of β-substituted to the α-substituted isomers of both alkyl naphthalenes and alkyl phenanthrene were used to assess the thermal maturity of sedimentary organic matter, which revealed high maturity level of Dhurnal, Pindori, Badin and Toot crude oils.